The Effects of Labor Characteristics on Firm Productivity: Empirical Evidence from Vietnam - Vo, Dut Van; Duong, Long Hoang; Tran, Man Minh Lam; Nguyen, Phu Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 4, 2021)
The paper investigates how labor characteristics affect firm productivity. Recent arguments on the relationship vary. On one hand, the labor force enhances firms’ financial strengths thanks to their manufacturing poductivity; on the other hand, such effects impede operations if overlooked. We proposed three hypotheses with views on such characteristics. First, leadership experience and second, a highly-trained firm labor force are both positively associated with firm productivity, whereas obstruction by labor laws has a negative effect on productivity. In a 123-firm dataset surveyed by the World Bank, the paper reveals that leadership experience and highly trained labor positively affect firm productivity while no statistical evidence was found of obstruction by labor laws. The major findings suggest that, firstly, labor-related theories are properly verified with different analysis settings; secondly, labor characteristics are the primary firm-level competitive power so they should be treated appropriately; thirdly, Vietnamese firms are not likely to be hindered by the country-level labor laws. However, the study constrains itself by not being conducted on a panel dataset to show the pattern over time, and by not treating the leadership experience in a proper, multifaceted way to capture their contribution comprehensively to the business-doing culture in Vietnam.